A Comparative Analysis on US Financial Stress Indicators - Manamperi, Nimantha (International Journal of Economics and Financial Issues, 2015)
This paper provides a comparative analysis on different financial stress indexes available for the United States. The main objective of these stress indexes is to provide detailed insights about the financial conditions in the U.S. economy. In general, all stress indexes indicated a very high financial risk during the 2008 financial crisis. Among all the Federal Reserve Bank financial stress indexes, the Kansas City Fed Financial stress index (KCFSI) and the St. Louis Fed Financial stress index (STLFSI) show considerable similarities during 2008 financial crisis. However the behavior of Chicago Fed’s National Financial Conditions Index (NFCI) and the Cleveland Fed’s Financial Stress Index (CFSI) were different. The stress indexes had responded to notable events with considerable shifts in their values. Indexes showed a significant increase for Fannie Mae/Freddie Mac and Lehman Brother bankruptcies while significant reductions for financial healing processes such as TARP, TALF and fed funds rate cuts during the great recession. If a researcher wants to study the financial conditions of the U.S. economy then these financial stress indexes should be the first choice. Keywords: Financial Stress Index; Financial Crisis; FED; US Economy; Recession JEL Classifications: E44: E58; G10